The Prevalence of Domesticated Geriatri Cats in Surabaya City at April-May 2019 - Rahmawati, Rr Indah Nur; Triakoso, Nusdianto; Ma'ruf, Anwar (Journal of Basic Medical Veterinary, 2021)
This study is beneficial to give information about population of domesticated geriatric cats in Surabaya period from April to May 2019. This study is also beneficial to give information about likely risks of domesticated geriatric cats in Surabaya City based on gender, cat breed, and cat's disease. The design of this study was Observational Retrospective using cross-sectional method. Sampling used stratified random sampling method. This study collected primary data and was analyzed descriptively using prevalence test and relative risks. That domesticated geriatric cats in Surabaya City period from April-May 2019, the oldest cats were written 17 years for male cats and 9 years for female cats. The prevalence of domesticated geriatric cats in Surabaya City period from April-May 2019 was 9 (7,5%). Geriatric cats distributed by the gender were 5 (4,2%) male and 4 (3,3%) female, where geriatric cats distributed by the cat breed were 5 (4,2%) pure breed, 4 (3,3%) mixed breed, and 0 (0%) domestic sample. The result of geriatric cats analysis based on gender showed that male cats had a change of 1,4 times higher compared to the female to reach geriatric, whereas based on cat breed it showed pure breed had a change 3,3 times compared to mixed breed to reach geriatric. On this study, the disease often appeared in domesticated geriatric cats in Surabaya City period from April -May 2019 were: on skin, respiration, digestion, and eyes. Based on relative risk analysis on geriatric cats, it had a change of gastrointetinal tract that was higher compared to other diseases.